The Effect of Organizational Commitment on The Characteristics of Management Accounting Information Systems Case Study at PT. Indo-Rama Synthetics Tbk - Indie Fauzi; Puji Mesti Rahayu; Veronica Christina (Greenation International Journal of Economics and Accounting, 2023)
Managers, in making a decision, it is necessary to have information that is in accordance with the characteristics of the management accounting system of each existing department to produce decisions that are in accordance with the needs and goals of the company. PT Indo-Rama Synthetics Tbk is one of the companies with a management accounting information system that is less integrated (integration), especially in the non- financial division. Meanwhile, good information can be generated from the organizational commitment inherent in every employee. This is because the assessment of organizational commitment can be a benchmark for how information is generated through the performance of each employee. This research is studied using Cook & Wall's theory of organizational commitment and Chenhall & Morris's theory of management accounting information system characteristics. This research was also conducted using quantitative methods with the type of casual explanatory research, with two main sources, namely secondary and primary sources, selected by purposive sampling technique with a sample of 80 people. The data generated in this study were also obtained from the results of questionnaires that had passed normality, validity, reliability, and hypothesis tests using the t and f tests assisted by SPSS version 23 software in analyzing them. The results of this study are (1) organizational identification influences the characteristics of management accounting information systems; (2) organizational involvement affects the characteristics of management accounting information systems; (3) organizational loyalty affects the characteristics of management accounting information systems; (4) organizational identification, organizational involvement, and organizational loyalty affect the characteristics of management accounting information systems.